(Mis)Education in Authoritarian Regimes: The Case of Eritrea - Zeraslasie Redie Shiker; Samson Maekele Tsegay (Education Sciences)
There is a debate on the role of education as a tool to challenge or enforce authoritarian attitudes. Many posit that education, particularly higher education, reduces authoritarianism; whereas vast research indicates that education can be used as an authoritarian tool for regime survival. This suggests that there are other intervening factors, such as the curriculum used, the teaching methodology implemented, and the educational administration employed, to securitise the academic space and impose authoritarian attitudes. Informed by the notion of hegemony and the banking concept of education, this article explores the nexus between education and authoritarianism, determining the role of education as an authoritarian tool for regime survival. We use the case of Eritrea, a country that has been under authoritarian government for more than two decades. The article is based on a literature review because it is risky to conduct an objective empirical study on the “politics of education” in Eritrea, given the country’s political sensitivity. The findings suggest that the Eritrean government politicises the curriculum and militarises secondary and higher education levels to create false consciousness and maintain power. The article contributes to advancing knowledge regarding the nexus of authoritarianism and education, helping people understand the state of the politics of education.